Substrate effect of coke particles on the structure and reactivity of coke/pitch mixtures in carbon anodes. (1st November 2016) - Chevarin, F.; Azari, K.; Ziegler, D.; Gauvin, R.; Fafard, M.; Alamdari, H.
Highlights: Comparison of the CO2 reactivity of anode and of three coke/pitch mixtures. Characterization of the pore size distribution between 0.0004 and 100 μm. Measurements of the pitch infiltration in coke particles with SEM. Abstract: Carbon anodes, used in the Hall-Héroult electrolysis process, are subject to an overconsumption caused by CO2 attack. Several attempts have been made to understand the mechanism of CO2 gasification based on the study of the reactivity of anode cores or anode constituents (coke, pitch and binder matrix). In this study, the specific surface area and the pore volume of carbon anode and of three coke/pitch mixtures were measured to understand properly the CO2 reactivity. Anode sample and three recipes of coke/pitch mixtures (100/0; 95/5 and 85/15, w/w) with a particle size of −1.4 + 1.0 mm were prepared. Argon adsorption and mercury infiltration were used to characterize the pore size distribution of the four samples. The specific surface area of anode and partially covered coke materials (95/5) were superior to that of the uncovered and totally covered particles (12 m 2 /g vs. 0.5 m 2 /g). Although the pore volume of the uncovered coke was high (0.45 cm 3 /g), the pore volume of totally covered coke was low (0.35 cm 3 /g). The pore volume of anode and partially covered coke were similar (0.4 cm 3 /g). A TG instrument was used to determine the apparent reaction rates of the four samples at 960 °C under CO2 atmosphere. It was remarked that the apparent reaction rate of coke/pitch mixtures was reduced with increasing the pitch content. The anode had an apparent reaction rate above that of totally covered particles but below the partially covered particles. Based on the apparent reaction rate and the pore analysis, the structure of an anode can be considered as a mixture of coke particles with different levels of pitch penetration. The pitch distribution in an anode paste could prevent the preferential gasification of some particles, thus possibly reducing dusting phenomenon.